2020
DOI: 10.1371/journal.pone.0234876
|View full text |Cite
|
Sign up to set email alerts
|

Health service utilization in immigrants with multiple sclerosis

Abstract: Background Access to neurology specialty care can influence outcomes in individuals with multiple sclerosis (MS), but may vary based on patient sociodemographic characteristics, including immigration status. Objective To compare health services utilization in the year of MS diagnosis, one year before diagnosis and two years after diagnosis in immigrants versus long-term residents in Ontario, Canada. Methods We identified incident cases of MS among adults aged 20-65 years by applying a validated algorithm to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…These findings suggest that patients of both groups had similar access to care and treatment opportunities across Italian MS Centres, independently of their birthplace, and that patients with a more aggressive disease at onset/diagnosis might have undergone a high-efficacy DMT. These data are in line with evidence from different HI Countries, supporting the belief that healthcare services and treatment strategies are equally available for MS patients who visit academic medical Centre or MS specialty Clinics [ 25 , 36 ].…”
Section: Discussionsupporting
confidence: 80%
“…These findings suggest that patients of both groups had similar access to care and treatment opportunities across Italian MS Centres, independently of their birthplace, and that patients with a more aggressive disease at onset/diagnosis might have undergone a high-efficacy DMT. These data are in line with evidence from different HI Countries, supporting the belief that healthcare services and treatment strategies are equally available for MS patients who visit academic medical Centre or MS specialty Clinics [ 25 , 36 ].…”
Section: Discussionsupporting
confidence: 80%
“…Datasets were linked by unique encoded identifiers and analyzed at ICES as previously described. 11 , 13 ICES (formerly known as the Institute for Clinical Evaluative Sciences) is an independent, non-profit research institute whose legal status under Ontario’s health information privacy law allows it to collect and analyze healthcare and demographic data, without consent, for health system evaluation and improvement. Data concerning immigrants arriving in Canada since 1985 are captured by the Immigration Refugees and Citizenship Canada’s (IRCC) electronic Permanent Resident Database.…”
Section: Methodsmentioning
confidence: 99%
“…Prior work from Ontario, Canada found that, as compared to long-term residents, immigrants with MS had a lower socioeconomic status (SES) and also differed in terms of health care use. For example, while the rates of outpatient neurology visits were somewhat lower in the year before MS diagnosis (adjusted rate ratio 0.93; 95% confidence interval [CI] 0.87–0.99), rates were higher in the year during and after MS diagnosis (adjusted rate ratios 1.17; 95% CI 1.12–1.23 and 1.16; 95% CI 1.10–1.23, respectively) 4 . Hospitalization rates were higher during the year of diagnosis, but lower post-diagnosis.…”
Section: Introductionmentioning
confidence: 99%